Teachers’ Protest Movements and Prospects for Teachers Improved Welfare in Uganda - Namara, Rose B.; Kasaija, Josephine (Journal of education and training studies, 2016)
Since the early 40s to today, teachers in Uganda organized themselves into unions and demanded for better conditions of service. Despite the long history of different forms of teachers’ protests, the contribution of these protests towards influencing the teacher’s welfare in the country is not sufficiently analyzed in the academic and policy circles. Up till now, it is not very clear what these protests have achieved. Written against the background of teachers’ protests in Uganda, this paper examines the effects of collective action of teachers on their welfare. Interviews with Uganda National Teachers Union Staff, Primary School Teachers, and Ministry of Education and Sports officials indicate that, teachers protests movement have enabled to show the public that teachers are unfairly remunerated and have also contributed to some incremental changes in teachers’ salaries and provision of some housing facilities by government. However, these protests have had minimal contribution to a policy and institutional framework that favour sustained improvement in teachers’ welfare as these protests are recurrent. The findings suggest that prospects for teachers’ protests to cause welfare changes in lives of teachers reside in proper mobilization of different categories of teachers as well as teachers’ ability to broadly link their welfare to professionalism and attainment of the education outcomes.
Keywords: teachers protests; teachers welfare; teachers professionalism; Uganda